Is it septic or cardiogenic shock? Papillary muscle rupture masquerading as sepsis. Issue 1 (21st January 2019) - Mukherjee, Ashes; Ravindranath, Syamnadh
Abstract: Introduction: Rupture of a papillary muscle is an extremely rare but catastrophic complication of an acute myocardial infarction. Survival is time dependent on the expedition of the patient from the area of presentation to the operating theatre for surgery. Diagnosis in the ED is possible within minutes of presentation if an echo is performed by an emergency physician skilled in echocardiography, as we demonstrate. Case presentation: We present a case of a 59 years male self‐presenting to the emergency department with undifferentiated shock. An EP performed echo directed us towards the rare but correct diagnosis. He was then transferred for percutaneous coronary intervention and surgical management. Conclusion: Often in the past a diagnosis made on coronary care units or post‐mortem, we believe this diagnosis in the future will be made more frequently at the bedside in emergency departments across the world as emergency physicians continue to incorporate echocardiography as a skill in their diagnostic armoury.